Karakterisasi dan Deteksi Cepat Bakteri Penyebab Penyakit Darah pada Pisang - Nur Edy; Siti Subandiyah; Christanti Sumardiyono; Jaka Widada (Universitas Gadjah Mada, 2011)
Blood disease of banana is one of the most serious banana disease in Indonesia. Although the disease has became the subject of quarantine it eventually spread and found in most provinces in Indonesia. The aim of this research were to identify the blood disease bacterium (BDB) using morphological observation, biochemical assay, pathogenicity testing of hosts range using infectivity titration and rapid detection by Polymerase Chain Reaction (PCR). The results showed that the blood disease bacterium could be differentiated from Ralstonia solanacearum race 2, the causal agent of Moko disease and R. solanacearum tobacco isolates. BDB isolates were not able to hydrolyze gelatin, Tween 80, starch, and were not able to produce nitrite from nitrate. They were only able to produce acid from galactose and glycerol. The pathogenicity test indicated that the BDB was only able to infect the banana/plantain and was not able to infect tomato, eggplant, and chili. Rapid detection using PCR method showed that the 121F/R primers was able to amplify the BDB genome and was not able to amplify the genome of R. solanacearum tobacco isolates.